Study of the effects of zinc pyrithione in biochemical parameters of the Polychaeta Hediste diversicolor: evidences of neurotoxicity at ecologically relevant concentrations - Nunes, Bruno (2022)
Nowadays there are various groups of biocidal chemical agents, which can be used in diverse areas, such as personal hygiene, disinfection, antiparasitic action, and also in antifouling mixtures or paints. The versatility and efficacy of some of these agents favors their use and ultimate release into the aquatic environment, where they may still exert toxic activity. Zinc pyrithione is classified as a metal biocide with bactericidal, algicidal, and fungicidal actions. It has been formulated in antifouling paints, which prevent the formation of biofilms in submerged structures, and has also been used for dermocosmetic purposes, in shampoos for the treatment of dandruff and seborrhea. Some of the uses of zinc pyrithione are responsible for its direct release as flakes that reach the bottom sediments, especially in estuarine areas. Considering this fate, the ecotoxicity assessment of its effects towards sediment organisms, namely Polychaetous species, is extremely important. The present study characterized the acute potential toxicity of zinc pyrithione in terms of parameters of oxidative stress (catalase, glutathione S-transferases (GSTs), and thiobarbituric acid reactive substances (TBARS)), and neurotoxicity (acetylcholinesterase) which were evaluated in individuals of the polychaete Hediste diversicolor. Regarding the results obtained, only the activity of GSTs and AChE was significantly altered in relation to non-exposed animals. This set of results indicates that oxidative stress did not occur.